2006
DOI: 10.1016/j.rmed.2005.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status, dietary energy intake and the risk of exacerbations in patients with chronic obstructive pulmonary disease (COPD)

Abstract: Loss of body weight, as a result of imbalance between increased energy demand and/or reduced dietary intake, is a common problem in patients with COPD. The aim of this investigation was to examine the relationship between nutritional intake, change in body weight and the risk of exacerbation in patients with COPD. The study comprised 41 patients who were hospitalised because of an exacerbation of COPD. The follow-up period was 12 months. Weight, height and lung function were measured at baseline. At the 12-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
1
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 35 publications
3
71
1
6
Order By: Relevance
“…Numerous studies, however, reported on the association between nutritional status and healthcare utilisation, focusing on patients hospitalised for a COPD exacerbation or predictors thereof. The studies showed that being undernourished in COPD is likely to be associated with longer in-patient hospital stays [107,108], a higher probability of being readmitted [62,109] and an increase in healthcare utilisation [110] in comparison with normally nourished patients. Three randomised controlled trials in COPD investigated the effects of nutritional supplementation on healthcare utilisation and/or costs [65,76,111].…”
Section: Cost-effectiveness Issuesmentioning
confidence: 99%
“…Numerous studies, however, reported on the association between nutritional status and healthcare utilisation, focusing on patients hospitalised for a COPD exacerbation or predictors thereof. The studies showed that being undernourished in COPD is likely to be associated with longer in-patient hospital stays [107,108], a higher probability of being readmitted [62,109] and an increase in healthcare utilisation [110] in comparison with normally nourished patients. Three randomised controlled trials in COPD investigated the effects of nutritional supplementation on healthcare utilisation and/or costs [65,76,111].…”
Section: Cost-effectiveness Issuesmentioning
confidence: 99%
“…The impact of dietary habits, nutritional status, and nutritional interventions is increasingly emphasized due to the possible role these may play on COPD outcome and prognosis [3,4]. Several studies have evaluated the impact of nutritional therapy in COPD patients [35].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of dietary habits, nutritional status, and nutritional interventions is increasingly emphasized due to the possible role these may play on COPD outcome and prognosis [3,4]. Several studies have evaluated the impact of nutritional therapy in COPD patients [35]. However, it is still unclear how specific dietary components may influence lung function [6] and important clinical outcomes in patients with COPD [7].…”
Section: Introductionmentioning
confidence: 99%
“…7 In addition, factors linked to socioeconomic status, such as respiratory tract infections, housing conditions, air pollution, and diet each contribute to the risk of having exacerbations. [8][9][10] Obviously, sex, age, and socioeconomic differences are important factors that can influence trend changes of COPD and exacerbations. Although these factors are well registered in general practice registration networks, their roles have not been well studied in COPD trend studies in primary care.…”
Section: Introductionmentioning
confidence: 99%